Fredrickson on Flourishing through Positive Emotions and Aristotle’s Eudaimonia - Pia Valenzuela (Conatus - Journal of Philosophy, 2022)
Is it possible to be happy without virtues? At least for the kind of enduring human happiness Aristotle bears, virtues are required (NE, I). In addition to virtues, some prosperity is necessary for flourishing, like having friends and minimal external goods. Nowadays, we witness different approaches to happiness – well-being – focusing on mental states – i. e. affective – usually without reference to moral issues, concretely moral dispositions, or virtues. At the crossroads of Philosophy and Psychology, the present article discusses the connection of happiness – well-being – and affective states by presenting Fredrickson’s theory of positive emotions, which has been criticised as approaching only hedonic well-being and therefore overlooking its eudaimonic aspects. In her approach, there is no reference to the good life connected to the human good, as in Aristotle’s ethics. However, there is instead an understanding of becoming a benevolent, a better person as a necessary human aspiration.